Draft Twelfth Five Year Plan (2012-17) and Annual Plan 2012-13 Volume II Government of Assam - Planning Commission (Planning Commission, 2012)
The Hill Areas of Assam comprising of two districts of Karbi Anglong and North Cachar Hills covers a geographical area of 15,322 sq km. Both are autonomous districts constituted under the provision of Sixth Schedule to the Constitution of India. Karbi Anglong district lies in the centre of the State of Assam and is bounded by Meghalaya state on the West, Nagaland and the district of Nagaon and North Cachar Hills on the North and South respectively. The district is located between latitudes 25° 33' and 26° 35' North and longitudes 92°10' and 93° 50' East. Karbi Anglong district has an area of 10,434sq km. The altitude varies from 600 mtrs in the North range to 900 mtrs in south range, while that of the valley area ranges from 75 mtr to 150 mtrs. Average maximum and minimum temperature of the district are 30°Celsius and 18° Celsius respectively.
Planning and Development Department Dispur, Assam Government of Assam